MUSLIM POLITICS AND DEMOCRACY: The Case of Indonesia (JOURNAL OF INDONESIAN ISLAM, 2007)
This article tries to scrutinize the complexity of dealing with the attempts at crafting democracy in Indonesia. It relates the issue of deploying religion among Muslim actors with the issue of state-market power-relations. With regard to the failing attempts of democratization, the writer argues that the problem does not lie with religion and Islam as such, but with democratisation that has run aground for a number of reasons. The real challenge is to develop more independent means of political representation. In his opinion, quoting Demos’ survey, the major task in the country at large is to build popularly rooted and representative civic-political organisations. He goes on to argue that while Muslim politics may promote measures against corruption, and neo-liberal actors may foster the rule of the laws they have shaped, both tendencies neglect independent popular representation to promote politically equal control of public affairs.